PENGARUH CITRA PERUSAHAAN, KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS NASABAH (Studi pada Nasabah Bank BTN Kantor Cabang Kudus) - Erina Dwi Hastuti, 14.05.51.0018; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
The purpose of this study is to analyze the influence of corporate image, trust, satisfaction on customer loyalty at PT. Bank Tabungan Negara (Persero) Tbk Kudus branch office. The study tested three hypotheses.The population of this research is customers PT. Bank Tabungan Negara of Kudus branch office. The sample size is 100 respondents withmethod convenience sampling. Data testing techniques used include validity test with product moment correlation, reliability test with alpha cronbach and multiple regression analysis. The results of the research are: Corporate image has a positive and significant impact on customer loyalty, trust does not affect customer loyalty and satisfaction has a positive and significant impact on customer loyalty.Keywords: Corporate Image, Trust, Satisfaction and Loyalty.